2009
DOI: 10.1037/a0014321
|View full text |Cite
|
Sign up to set email alerts
|

Speech recognition and working memory capacity in young-elderly listeners: Effects of hearing sensitivity.

Abstract: Young normal-hearing listeners and young-elderly listeners between 55 and 65 years of age, ranging from near-normal hearing to moderate hearing loss, were compared using different speech recognition tasks (consonant recognition in quiet and in noise, and time-compressed sentences) and working memory tasks (serial word recall and digit ordering). The results showed that the group of young-elderly listeners performed worse on both the speech recognition and working memory tasks than the young listeners. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 75 publications
9
29
2
2
Order By: Relevance
“…Arehart et al (2013) identified WM as a significant factor in listeners' recognition of sentences in babble processed with frequency compression, accounting for 29.3% of the variance in recognition scores. These findings are consistent with numerous other reports of correlations of verbal WM and speech perception for patients, tested in unaided and/or aided conditions, when the speech has been degraded by peripheral hearing loss (Cervera, Soler, Dasi, & Ruiz, 2009), noise (Lunner & Sundewall-Thorén, 2007;Rudner et al, 2008), spectral degradation (Schvartz, Chatterjee, & Gordon-Salant, 2008), or dynamic range compression (Piquado, Benichov, Brownell, & Wingfield, 2012;Rudner, Rönnberg, & Lunner, 2011). Thus, there is generally support for the idea that verbal WM abilities are related to speech recognition skills in patients with hearing loss listening under noisy conditions and in participants with normal hearing (NH) listening to degraded speech.…”
Section: Wm Hearing Loss and Speech Recognitionsupporting
confidence: 93%
“…Arehart et al (2013) identified WM as a significant factor in listeners' recognition of sentences in babble processed with frequency compression, accounting for 29.3% of the variance in recognition scores. These findings are consistent with numerous other reports of correlations of verbal WM and speech perception for patients, tested in unaided and/or aided conditions, when the speech has been degraded by peripheral hearing loss (Cervera, Soler, Dasi, & Ruiz, 2009), noise (Lunner & Sundewall-Thorén, 2007;Rudner et al, 2008), spectral degradation (Schvartz, Chatterjee, & Gordon-Salant, 2008), or dynamic range compression (Piquado, Benichov, Brownell, & Wingfield, 2012;Rudner, Rönnberg, & Lunner, 2011). Thus, there is generally support for the idea that verbal WM abilities are related to speech recognition skills in patients with hearing loss listening under noisy conditions and in participants with normal hearing (NH) listening to degraded speech.…”
Section: Wm Hearing Loss and Speech Recognitionsupporting
confidence: 93%
“…Different studies have already reported on the interplay between sensory and cognitive functioning (e.g., Cervera et al, 2009;McCoy et al, 2005;Murphy et al, 2000;Pichora-Fuller et al, 1995;Rabbitt, 1991;Schneider et al, 2000Schneider et al, , 2002Verhaegen et al, 2014;Wingfield et al, 2005). Most of them, however, investigate memory performance in persons with reduced hearing thresholds and control for differences in peripheral hearing status in various ways.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them, however, investigate memory performance in persons with reduced hearing thresholds and control for differences in peripheral hearing status in various ways. Cervera et al (2009), for example, investigate performance on auditory working memory tasks (digit ordering and serial word recall) and speech processing performance while controlling for hearing statistically. By applying pure tone averages as a covariate in an ANCOVA model, diminished performance of young old participants with presbycusis (55-65 years) disappears when compared with young participants without hearing impairment (19-25 years).…”
Section: Discussionmentioning
confidence: 99%
“…19,20,21 Yaşa bağlı işitme kayıplarının en önemli özelliği, özellikle saf ses işitme eşiklerinde düşüş ve konuşmayı anlamama sorunlarıyla karakterizedir. İlerleyen yaşla birlikte kokleada tiz seslerin duyulduğu 1000 Hz ve üzerindeki frekanslarda işitme kaybının daha fazla olduğu görülmektedir.…”
Section: Yaşlılık Döneminde İşitme Kaybı Nedenleri Ve öZellikleriunclassified
“…2009 yılında yapmış oldukları çalışmada, normal işitmesi olan gençlerle, yaş aralığı 55-65 yaş arasında değişen ve normale yakın dereceden orta derecede işitme kaybına sahip olan genç-yaşlı grup arasında farklı konuşmayı ayırt etme işlemlerini değerlendirmişlerdir. 21 Genç gruba göre, genç yaşlı grupta konuşmayı anlama ve kelimeyi ayırt etme işlemlerinde daha kötü performans gösterdiklerini rapor etmişlerdir. Bu çalışmada bilişsel işlemlerde yaşla birlikte görülen azalmanın konuşma algılamasında da kötüleşmeye sebep olduğu belirtilmiştir.…”
Section: Yaşlılık Döneminde İşitme Kaybı Nedenleri Ve öZellikleriunclassified